IMPLEMENTATION OF THE STUDENT FACILITATOR AND EXPLAINING (SFE) MODEL TO IMPROVE STUDENT LEARNING RESULTS ON UNITY AND UNITY IN THE NKRI IN CLASS XI IPS 2 SMA NEGERI 1 GEDEG - Agus Sarwo Edi (Sean Institute, 2022)
The purpose of learning PPKn in SMA A is to prepare you as students to be able to play a role as good citizens, namely citizens who are intelligent, skilled and characterized and loyal to the nation and state of the Republic of Indonesia by reflecting on it in the habit of thinking and acting in accordance with Pancasila and the 1990 Constitution of the Republic of Indonesia. 1945 Therefore, learning needs to be given in a serious, interesting way so that complete learning outcomes can be achieved. The results of initial observations at SMA Negeri 1 Gedeg obtained the daily test scores for class XI IPS 2 totaling 32 students , who did not complete the study amounted to 1-2 students with a percentage of 60% completeness. Based on this description, it shows that the learning outcomes for unity and unity within the Unitary State of the Republic of Indonesia, students of SMA Negeri 1 Gedeg are not good at having low learning outcomes with a completeness percentage of 62.1%. Low learning outcomes due to the application of inappropriate learning models, passive students in learning, no assessment of assignments. The purpose of this study was to analyze the increase in learning outcomes for class XI IPS 2 SMA Negeri 1 Gedeg through the application of the Student facilitator and explaining (SFE) learning model. To improve student learning outcomes on unity and integrity in the Unitary State of the Republic of Indonesia, a classroom action research was conducted which consisted of two cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The subjects of this study were students of SMA Negeri 1 Gedeg class XI IPS 2 academic year 2019/2020 consisting of 32 students . The data collection instruments in this study were evaluation questions for the cognitive domain which were carried out at the end of each cycle and observation sheets for the affective and psychomotor domains. Based on the results and discussion, it can be concluded that learning using the Student Facilitator and Explaining (SFE) learning model makes it easy for teachers to learn, makes learning centered on students, completes learning outcomes, and can teach and train student character behavior. The implementation of lesson plans is in good category with an average score of 3.12 in the first cycle and 3.3 2 in the second cycle. Student activity reached 85.26% in the first cycle and rose to 92.22%. In the aspect of scientific behavior both cycles are in the good category. Mastery learning outcomes also showed an increase, from 71.88 % in the first cycle to 90.63 % in the second cycle .